THE PRINCIPAL'S STRATEGY IN IMPROVING THE QUALITY OF TEACHING STAFF DURING THE PANDEMIC - Marlin, marlin; Zulkifli, M (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2024)
This study aims to examine and analyze the principal's strategy in improving the quality of teaching staff during the pandemic at Sambalagi Elementary School from the principal's strategy, the quality of teaching staff and the principal's policy regarding the pandemic. The object of this research is the principal and teachers at Sambalagi Elementary School. This research uses qualitative research. Data collection methods were carried out by means of observation, interviews and documentation. Data analysis through the process of collecting informants, reducing data, presenting data and drawing conclusions and verification and testing data validity through data triangulation (sources, techniques and time). The results showed that: 1) the principal's strategy is carried out by carrying out quality improvement of teaching staff in three months once a week followed by two teaching staff (teachers): 2) the current quality of teaching staff at Sambalagi Elementary School still needs to be improved: 3) the principal's policy regarding the covid-19 pandemic is to continue carrying out activities by complying with health protocols, namely wearing masks, washing hands, and maintaining physical distancing